Triterpenoids from the leaves of Alphitonia xerocarpus Baill and their biological activity. (September 2016) - Muhammad, Dima; Lalun, Nathalie; Bobichon, Hélène; Le Magrex Debar, Elisabeth; Gangloff, Sophie C.; Nour, Mohammed; Voutquenne-Nazabadioko, Laurence
Abstract: Ten previously undescribed triterpenoid saponins and a previously undescribed nor lupane triterpenoid were isolated, with three known saponins, four known flavonoids, two known lupane derivatives, sitosterol and 6′-heptadecanoyl-3- O-β- d -glucopyranosylsitosterol from the leaves of Alphitonia xerocarpus (Rhamnaceae), an endemic tree of New Caledonia. The chemical structures of the purified compounds were identified by nuclear magnetic resonance and mass spectrometry. The isolated compounds were tested for their antioxidant, antityrosinase, antibacterial and cytotoxic activity. The aqueous methanol extract showed antioxidant activity (DPPH assay) due to the presence of rutin. Ceanothenic acid showed good cytotoxic activity against a KB cell line (IC50 = 2.6 μM) and antibacterial activity against Staphylococcus aureus and Enterococcus faecalis with MIC values of 8 and 16 μg/mL, respectively. The previously undescribed 29-hydroxyceanothenic acid exhibited moderate cytotoxic activity (IC50 = 10 μM), good antibacterial activity against S. aureus (MIC = 4 μg/mL) and moderate antibacterial activity against E. faecalis (MIC = 16 μg/mL). Graphical abstract: Triterpenoid saponins, lupane triterpenoids and flavonoids were isolated from the leaves of Alphitonia xerocarpus . Their antioxidant, antibacterial and cytotoxic activity were measured. Highlights: Ten triterpenoid saponins were isolated from Alphitonia xerocarpus. One nor-lupane triterpenoid was previously undescribed. The aqueous methanol extract showed good antioxidant activity (DPPH assay). Two compounds showed antibacterial and cytotoxic activity.